La reconstruction des fermes dans le département de l’Aisne après 1918 - Jean-Charles Cappronnier; Franck Delorme (In Situ)
From a geographical point of view the Aisne department is completely artificial; the territory consists of the merging of a detached tip of Île-de-France (Valois and Meldois), a part of Champagne (Brie Champenoise) and the south of Picardie (Soissonnais, Laonnois, Thiérache and Vermandois). This administrative aggregation naturally goes hand in hand with a mosaic of terrains which differ geologically. It is this very heterogeneity which makes the Aisne department, as regards rural architecture, a case study worthy of interest as it displays varied and pronounced characteristics. During the First World War, the Aisne, essentially rural with the exception of Soissons and Saint-Quentin, saw its villages and farms devastated in the fighting. It is therefore an “ideal” field for implementing deliberations concerning the improvement of agricultural productive capacity and its architecture.